Makna Simbolis pada Unsur Visual Kostum Tari Topeng Babakan Cirebon Keni Arja di Desa Slangit - Ayoeningsih Dyah (Journal of Visual Art and Design, 2007)
Mask dance is one of the traditional performing arts that has grown and developed ever since the Hindu period. At the beginning, this artistic performance serves as the medium in the ceremonial tradition related to the ritual of elderly summon, for giving blessings and provide salvations.  In the Islam period, the performance was used by Sunan Gunung Djati as a media of religious endeavor to show the phase in human's beliefe. In this special type of performance, the dancer wears five character masks: Panji, Pamindo, Rumyang, Patih and Klana, along with their equipments, such as costumes, clothes, and headdress called sobrah. Although it looks visually simple, its provide lots of symbolical values that are related to the growing period of arts, where major philosophies from the two grand religions (Hindu and Islam) collided. It is also related to the concept of Mandala, a primordial discourse of Indonesian society. This study focuses in analyzing the symbolic meaning of visual elements from the babakan dance's costume, which was used by Keni Arja in the year of 2006. It is found that inside Keni Arja's costume there are full varieties of forms, motives, and colors. For instance, the figure of Panji, Pamindo, Rumyang, and Patih wear a tie; however Klana wears ombyok to cover the chest. Patih's figure is no longer using sobrah as headdress, instead it uses peci-bendo and glasses. Results of analysis indicate that there are several changes on the visual elements inside mask-dance costume, especially in the element of form among ornament of sobrah, the material of sobrah, the costume colors of every character, and the motive of kain. Interestingly, Keni Arja keeps using some traditional elements, such as headdress (called sobrah) and a cloth piece to cover below. This indicates that traditional dancer still obeys the old form, which refers to the early birth of this artistic performance, as a way to keep magical values of the performing arts.